The Entrepreneurship Training and Mentoring in Dusun Tengah, Padurungan Village, Tanah Merah District, Bangkalan Regency - Islamiyah; Moh. Sholeh; Sulipah; Ali, Lailatul Fadilah; Anisaturrohmah; Honipah; Aisyahanis; Ririn (LP3M STAI At-Tahdzib Jombang, 2025)
Padurungan Village, Tanah Merah District, Bangkalan-Madura Regency has a number of residents, the majority of whom are farmers. So the income of the Padurungan village community is from farming, and only once a year due to very limited land conditions. Therefore, we aim to carry out community service to improve the economy of the community with the Title Entrepreneurship Training and Mentoring in Dusun Tengah Village Padurungan District, Tanah Merah District, Bangkalan Regency. The method of this activity is participatory action research (PAR). Of course, the researchers went directly to the field to analyze and collect data. And the researchers found that the Padurungan village community, apart from farming, also grew crops such as: cucumbers, cassava, sesame seeds, peanuts, corn and others. This can be traded in the market, the rest is consumed personally. The researcher conducted a preliminary study to provide an understanding of how to improve an efficient and effective economy in accordance with the natural resources in the village. And in this case, the formation of a home industry is very relevant, namely a home business producing goods or a small company, because this type of activity is centered at home, the existence of a home industry will bring significant changes to improving the quality of life of the community. In this, efforts are needed to protect and develop this business. The research used in the study is a qualitative method. with the existence of a home industry, cassava leaf chips become a strategy in the Miro Business and can increase the income of the community in Padurungan Village.